Psychological contributors to the frail phenotype: The association between resilience and frailty in patients with cirrhosis. Issue 1 (21st July 2020) - Wong, Randi J.; Mohamad, Yara; Srisengfa, Yanin T.; Kent, Dorothea S.; Seetharaman, Srilakshmi; Shah, Rupal J.; Lai, Jennifer C.
Abstract : We examined whether a key psychological trait—resilience, defined as one's ability to recover quickly from difficulties—contributes to the frail phenotype in patients with cirrhosis. Included were 300 adult patients with cirrhosis who underwent outpatient physical frailty testing using the Liver Frailty Index and resilience testing using the Connor‐Davidson Resilience Scale (CD‐RISC). The Liver Frailty Index was categorized as robust, prefrail‐robust, prefrail‐frail, and frail; CD‐RISC was categorized using population norms as: least, less, more, and most resilient. Linear regression was used to assess factors associated with frailty (by the Liver Frailty Index per 0.1 unit change). Among the most resilient, only 10% were frail; among the least resilient, 29% were frail. In univariable analysis, resilience was strongly associated with the Liver Frailty Index (coef = −0.13 per point increase; 95% confidence interval [CI], −0.20 to −0.60; P  < .001) and remained significantly associated with frailty in multivariable adjustment (coef = −0.13, 95% CI −0.19 to −0.07; P  < .001). Low resilience is strongly associated with the frail phenotype in patients with cirrhosis. Given that resilience is modifiable, our data suggest that effective interventions to mitigate frailty should include strategies to build resilience in patients with low baseline resilience. Abstract : Psychological resilience is strongly associated with lower rates of frailty in patients with cirrhosis, suggesting that the Liver Frailty Index may capture aspects of frailty beyond the physical.